Anonymous Internet Creative Writing as a Means of Modern Communication (On the Question of the Study of Anonymous Internet Parodies) - Belovodskaja, Anastasija (Respectus Philologicus, 2012)
The focus of the whole “Internet space” on communication and the availability of technical possibilities makes the spread of information on the Internet practically unrestricted. This in turn leads to the transformation of the Internet communication model, which could be represented as “WE” – ”WE” in relation to anonymous Internet texts, when not an individual, but “the faceless crowd” or “Anonymous” appears to be both the sender and the addressee of the message. This article points out that in anonymous creative writing, even “mute” text sending and its placement on Internet diary pages is an expression of a particular attitude; in the case of parody, it is also a means of rethinking the events within the context provided by the parody. Alongside parody’s entertaining character, which contributes to the text’s attractiveness and ease of perception, it can be a powerful weapon allowing the author to reframe a particular situation. At the same time, the monitoring of anonymous Internet parodies from the point of view of the underlying prototexts may be a means of identifying the most important precedent phenomena, which are used repeatedly and form a part of the Internet-users’ collective cognitive base. The transformations of texts that occur when the texts are parodied reflect corresponding changes in the consciousness of their anonymous author-users. Thus, the analysis of anonymous “Internet creative writing” may appear to be quite an effective way to study the processes of social consciousness, both declared overtly and covert.
Keywords: Internet discourse; anonymous Internet creative writing; Internet folklore; parodies; prototexts; communication model; reframing